CARACTERIZAÃ‡ÃƒO DE CULTIVARES DE GERGELIM (ð˜šð˜¦ð˜´ð˜¢ð˜®ð˜¶ð˜® ð˜ªð˜¯ð˜¥ð˜ªð˜¤ð˜¶ð˜® L.) - Nakagawa, JoÃ£o; Banzatto, N. V.; Savy Filho, Ã‚ngelo (REVISTA DE AGRICULTURA, 2020)
CARACTERIZAÃ‡ÃƒO DE CULTIVARES DE GERGELIM (ð˜šð˜¦ð˜´ð˜¢ð˜®ð˜¶ð˜® ð˜ªð˜¯ð˜¥ð˜ªð˜¤ð˜¶ð˜® L.)